Poor Women’s Access to Antenatal Care and Childbirth Services in Indonesia: Case Study in Five Districts - Dyan Widyaningsih; Elza Samantha Elmira; Andi Misbahul Pratiwi (Yayasan Jurnal Perempuan, 2019)
The health of pregnant women often becomes an indicator of human development. On the other hand, the fact of the high maternal mortality rate, raises questions related to the government’s attention to the health of pregnant women, especially women in poor areas. This article focuses on poor women’s access to health services for antenatal care and childbirth in five regencies in Indonesia. The aspects studied include the availability of health services for antenatal care and childbirth, poor women’s access to these services, and supporting factors/actors and barriers to poor women’s access to health services. This article showed that the availability of health facilities is not always in line with the increased awareness of pregnant women to access these services. Road infrastructure condition, distance, and cost to access health service still remain a challenge. Meanwhile, the policy of incentives and disincentives to traditional birth attendants has an influence on the increasing number of pregnant women who check their pregnancies and childbirth at health facilities. Thus, health issues of pregnant women and safe childbirth require a different effort. Aspects of the local context and supporting infrastructure also require serious attention.